2022
DOI: 10.1038/s41598-022-18730-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fullerene motion on thermally activated gold substrates with different shapes

Abstract: In the current study, the regime of motion of fullerene molecules on substrates with different shapes at a range of specific temperatures has been investigated. To do so, the potential energy of fullerene molecules was analyzed using the classical molecular dynamics method. C20, C36, C50, C60, C72, C76, C80, and C90 fullerene molecules were selected due to their spherical shapes with different sizes. In addition, to completely analyze the behavior of these molecules, different gold substrates, including flat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…3, which shows a considerably large motion of C 60 in the XY-plane, in line with the previous theory work on the diffusion of C 60 on the substrate of a low-dimensional semiconductor 43,44 and metal. 45 In order to gain further insights into the structural dynamics, we present in Fig. 3c and d the partial vibrational density of states (VDOS) of the two systems, calculated by discrete fast Fourier transform of the velocity-velocity autocorrelation function obtained from ab initio MD:…”
Section: Resultsmentioning
confidence: 99%
“…3, which shows a considerably large motion of C 60 in the XY-plane, in line with the previous theory work on the diffusion of C 60 on the substrate of a low-dimensional semiconductor 43,44 and metal. 45 In order to gain further insights into the structural dynamics, we present in Fig. 3c and d the partial vibrational density of states (VDOS) of the two systems, calculated by discrete fast Fourier transform of the velocity-velocity autocorrelation function obtained from ab initio MD:…”
Section: Resultsmentioning
confidence: 99%
“…Computational modeling enables us to explore the physicochemical and biological phenomena. [53][54][55][56][57][58][59][60] The MD simulation method was adopted from the literature and was derived from a theoretical nano-scale viewpoint of the experiments. The MTT assay was carried out using L929 cells on a chitosan/ gelatin composite hydrogel scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…In the prior models of nano-machines, three or four-wheeled nano-machines in which C 60 was utilized as a wheel were fabricated significantly 12 , 16 , 17 . C 60 is a well-known molecule that quite a few experimental and computational studies were reported its motion on different substrates 6 , 17 , 18 . Additionally, since all reported nanocars and nanotrucks employed with C 60 fullerene wheels, it seems that the comparison between C 60 and the nano-machines not only provides us with a better understanding of these machines, but may bring a breeding grounds for finding a correlation between them as well 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%